1993
DOI: 10.1172/jci116586
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between skeletal muscle lipoprotein lipase activity and 24-hour macronutrient oxidation.

Abstract: A low ratio of whole-body 24-h fat/carbohydrate (CHO) oxidation has been shown to be a predictor of subsequent body weight gain. We tested the hypothesis that the variability of this ratio may be related to differences in skeletal muscle metabolism. Since lipoprotein lipase (LPL) plays a pivotal role in partitioning lipoprotein-borne triglycerides to adipose (storage) and skeletal muscle (mostly oxidation), we postulated that a low ratio of fat/CHO oxidation was associated with a low skeletal muscle LPL (SMLPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(51 citation statements)
references
References 30 publications
4
45
1
Order By: Relevance
“…They reported data for endurance athletes in the trained state and after two-weeks of detraining; LPL activity in muscle decreased markedly with detraining, alongside a clear increase in the activity of this enzyme in adipose tissue. 77 These ®ndings, and a recent report of an association between low skeletal muscle LPL activity and increased systemic respiratory quotient (hence reduced fat oxidation), 78 demonstrate the potential of exercise with the body's large muscles to in¯uence body composition in the longterm. This may be most dramatically demonstrated by comparison of responses to a high fat diet in mice; the profound increase in fat mass induced in normal animals by this diet was largely avoided in transgenic mice which over-expressed skeletal muscle LPL.…”
Section: Exercise and Postprandial Lipid And Lipoprotein Metabolismmentioning
confidence: 69%
“…They reported data for endurance athletes in the trained state and after two-weeks of detraining; LPL activity in muscle decreased markedly with detraining, alongside a clear increase in the activity of this enzyme in adipose tissue. 77 These ®ndings, and a recent report of an association between low skeletal muscle LPL activity and increased systemic respiratory quotient (hence reduced fat oxidation), 78 demonstrate the potential of exercise with the body's large muscles to in¯uence body composition in the longterm. This may be most dramatically demonstrated by comparison of responses to a high fat diet in mice; the profound increase in fat mass induced in normal animals by this diet was largely avoided in transgenic mice which over-expressed skeletal muscle LPL.…”
Section: Exercise and Postprandial Lipid And Lipoprotein Metabolismmentioning
confidence: 69%
“…This may be due to enhanced uptake of dietary fatty acids by the greater adipose tissue mass of overweight subjects, in whom lipoprotein lipase activity is increased. 21 Release of exogenous fatty acids into plasma has previously been shown to be defective in obese women compared to normal weight women, 20 possibly due to greater uptake by elevated AT stores. The results from this study show that fat oxidation and EE were enhanced to a greater degree with MCT consumption compared to LCT in men of lower BW.…”
Section: Discussionmentioning
confidence: 99%
“…Crosssectional studies demonstrated that the 24 h RQ correlated negatively with skeletal muscle lipoprotein lipase, 35 b-hydroxyacyl-CoA dehydrogenase, adenylokinase and creatine kinase activities. 36 Whether the preferential pattern of fuel utilisation by an individual is determined by skeletal muscle enzyme activity or by substrate availability is, as yet, unknown ± although the size of body fat stores and insulin sensitivity/ resistance are known to modulate circulating free fatty acid concentrations and are independent factors predicting percentage fat oxidation.…”
Section: Discussionmentioning
confidence: 99%